The Resort Police of Surabaya Strategy in Preventing Transnational Terrorism Crime Post-Bomb Explosion in Surabaya City in 2018 - Khairunnisa, Brilliant Windy; Rohman, Abid (Jurnal Ilmiah Widya Sosiopolitika; Vol 5 No 1 (2023): DIPLOMASI DAN ISU-ISU INTERNASIONAL, 2023)
Transnational terrorism crime acts have become a security issue that threatens Indonesia which cannot be separated from the responsibility of the police as law enforcers and community security guards. As for the case of bomb detonations carried out by terrorists in the city of Surabaya in 2018, involving the Intelligence and Security Unit at the Resort Police of Surabaya to initiate, accompany, and end any operational activities, especially in terms of securing international acts of terrorism in Surabaya after the bomb detonation in order to avoid a similar incident again in the future. This article focuses on explaining how the strategy of the Resort Police of Surabaya in preventing transnational terrorism crime after the bombing in the city of Surabaya last 2018. In the discussion, the writer uses a qualitative-exploratory research method based on primary and secondary data reviewed in the non-traditional security concept. The results of this study indicate that the Resort Police of Surabaya (Polrestabes) has several strategies for the prevention of similar cases, including the development of institutional policies and systems, strengthening the capacity of police personnel, expanding internal and external cooperation networks, and increasing the intensity of guidance to former perpetrators of terrorism criminal acts and their families to return to their normal life which is carried out regularly in supporting efforts to prevent transnational terrorism crime acts, especially in the big city of Surabaya Keywords : Strategy, Prevention, Crime Acts, Transnational Terrorism.